Goal-Directed Fluid Therapy Based on Stroke Volume Variation in Patients Undergoing Major Spine Surgery in the Prone Position: A Cohort Study. Issue 18 (15th September 2016) - Bacchin, Maria Renata; Ceria, Chiara Marta; Giannone, Sandra; Ghisi, Daniela; Stagni, Gaetano; Greggi, Tiziana; Bonarelli, Stefano
Abstract : Study Design: A retrospective observational study. Objective: The aim of this study was to test whether a goal-directed fluid therapy (GDFT) protocol, based on stroke volume variation (SVV), applied in major spine surgery performed in the prone position, would be effective in reducing peri-operative red blood cells transfusions. Summary of Background Data: Recent literature shows that optimizing perioperative fluid therapy is associated with lower complication rates and faster recovery. Methods: Data from 23 patients who underwent posterior spine arthrodesis surgery and whose intraoperative fluid administration were managed with the GDFT protocol were retrospectively collected and compared with data from 23 matched controls who underwent the same surgical procedure in the same timeframe, and who received a liberal intraoperative fluid therapy. Results: Patients in the GDFT group received less units of transfused red blood cells (primary endpoint) in the intra (0 vs . 2.0, P = 0.0 4) and postoperative period (2.0 vs . 4.0, P = 0.003). They also received a lower amount of intraoperative crystalloids, had fewer blood losses, and lower intraoperative peak lactate. In the postoperative period, patients in the GDFT group had fewer pulmonary complications and blood losses from surgical drains, needed less blood product transfusions, had a shorter intensive care unit stay, and a faster return of bowel function. We found no difference in the total length of stay among the two groups. Conclusion: Our study shows that application of a GDFT based on SVV in major spine surgery is feasible and can lead to reduced blood losses and transfusions, better postoperative respiratory performance, shorter ICU stay, and faster return of bowel function. Level of Evidence: 3